Morfología del polen en el área de influencia del Monumento Arqueológico de Salapunku del Santuario Histórico de Machupicchu, Cusco - Perú - Moriano-Huillca, Melanie (2024)
The description of the pollen grains of the Bromeliaceae, Fabaceae and Solanaceae families present in the Salapunku-SHM Archaeological Monument was carried out to determine their characters for taxonomic purposes and establish a reference base for subsequent paleopalynological studies that can be carried out in this zone. The palynological material was obtained from the collection of flowering specimens of the families: Bromeliaceae, Fabaceae and Solanaceae, between the months of September-December 2019 and February-March 2020. For the treatment of pollen samples, the Erdtman (1960) acetolysis technique and palynological characters such as: polar and equatorial diameter, openings, scope, size and sculptural elements of the sporodermis were considered. Three species of the Bromeliaceae family, seven species of the Fabaceae family and five species of the Solanaceae family were analyzed. The results showed that the palynological characters with the greatest predominance according to the type of grain are monads, radial symmetry, isopolar, prolate-sphe- roidal and prolate shape, semi-angular scope, medium size, tricolporate opening and reticulated ornamentation. Through this work and the bibliographic review, it was concluded that the families evaluated retain similarities in pollen morphology, being of taxonomic importance for paleobotanical studies.